Motivation and incentives in an online labor market - Sebastian Fest; Ola Kvaløy; Petra Nieken; Anja Schöttner (Center for Economic Studies and ifo Institute (CESifo), 2019)
In this paper we present results from a large scale real effort experiment in an online labor market investigating the effect of performance pay and two common leadership techniques: Positive expectations and specific goals. We find that positive expectations have a significant negative effect on quantity - and no effect on quality - irrespective of how the workers are paid. On average, workers who receive positive expectations before they start to work, have a five percent lower output than those who do not. Goal-setting has no significant effect, neither on quantity nor quality. Performance pay, in contrast, has a strong positive effect on quantity, although we find no difference between high and low piece rates. Finally, we find no evidence of a multitask problem. Piece rates have no negative effects on the quality of work, even if it is fully possible for the workers to be less accurate and thereby substituting quality for higher quantity.
Keywords: C93; M52; J33; 330; non-monetary motivation; performance pay; field experiment